Daiktavardžio kamienų bei giminių variantai baltų kalbose (Ide. ir bendroji baltų bei slavų kalbų leksika) - Stundžia, Bonifacas (Baltistica, 1994)
GENDER-VARIANT NOUNS IN BALTIC LANGUAGES (OLD INDO-EUROPEAN AND COMMON BALTO-SLAVONIC VOCABULARY)On the basis of historical and etymological analysis of 55 gender-variant nouns of the old IE and common Balto-Slavonic vocabulary of Baltic languages, the following conclusions can be drawn:1. The existence of ǒ-//ā-stem diatopical gender-variants, the ǒ-stem member of which is, as a rule, more archaic, is characteristic of the analysed vocabulary. The variation of i̯ǒ-//i̯ā-stem nouns is very rare, and the * ii̯ǒ-//ē-stem variants have not been found at all.2. Approximately half of the variants are deverbatives, the majority of which are abstract or former abstract nouns (deadjectival abstract nouns are rare).3. The variation of ǒ-//ā-stem nouns (first of all the abstract ones) is an archaic phenomenon inherited from the IE dialects. The origin of this phenomenon could be related to the competition of the two derivational models (one with thematic vowel ǒ, and the other with thematic vowel ā) of nomina actionis.4. The (i̯)ǒ-//(i̯)ā-stem noun variants have increased in number because of the pluralization of nomina ā/ǝ-collectiva, the process which stimulated the oxytonization of ǒ-stem nouns and maybe accelerated the disappearance of the neuter gender in Baltic languages. In its own turn, the latter process preconditioned the appearance of the new gender-variant nouns.
Keywords: baltų kalbos; daiktavardis